Aulin V., Bobrytskyi V., Tikhii A. Providing self-form parts with cutting elements in their manufacture. - Аулін, В.В.; Бобрицький, В.М.; Тихий, А.А. (Problems of Tribology, 2014)
To ensure self-form cutting elements in the operation of a technology manufacturing business with the use of concentrated energy flows. It is shown that the application of technology, a reduction in manufacturing operations and improve the reliability and durability of parts. The changes shape and size of the work wear of tillage machines manufactured by different technologies.